Effect of isofebrifugine on the proliferation and invasion of human gastric cancer cells via MMP - Xu, Jin; Wu, Jianbo; Tang, Chuankang (Cellular and Molecular Biology, 2020)
Gastric cancer (GC) is one of the most common fatal cancers among gastrointestinal malignancies. At present, the treatment of gastric cancer involves a combination of surgery and chemotherapy. Isofebrifugine (IFE) is an alkaloid with many biological properties. In this study, results from MTT, scratch and invasion assays showed that IFE significantly inhibited the proliferation, migration and invasion of SGC7901 gastric cancer cells. Through RT-PCR and Western blot experiments, it was revealed that IFE significantly inhibited the mRNA and protein expressions of MMP-2, MMP-9 and SDF-1 which are closely related to cancer invasion and metastasis. Thus, IFE possesses anti-gastric cancer properties.